PENGARUH GAJI, KONDISI KERJA DAN PROGRAM PELAYANAN BAGI KARYAWAN TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN DI PT. BALIAN MEDIA ONLINE NUSANTARA - SUDARNAYA, I KETUT; MARGARETA, NI NYOMAN RUTH (GANEC SWARA, 2023)
The purpose of this study was to determine the effect of salary, working conditions and service programs for employees on work productivity of employees at PT. Balian Media Online Nusantara. The population in the study was 55 people while the sample in this study was a saturated sample. Sampling technique when all members of the population are sampled. Data collection method by using a questionnaire, technique data analysis techniques using the SPSS application. The research results show that the results of testing hypothesis 1 show that salary has a positive and significant effect on work productivity. The results of testing hypothesis 2 show that working conditions have a positive and significant effect on work productivity. The second hypothesis is accepted. The results of testing hypothesis 3 show that service programs for employees have a positive and significant effect on work productivity